HUBUNGAN PARITAS DAN USIA GESTASI DENGAN HIPEREMESIS GRAVIDARUM DI PRAKTEK MANDIRI BIDAN - Zalni, Rummy Islami; Risandy, Resty Ridhany; Anita, Wan (Ensiklopedia of Journal, 2024)
Pregnancy is a physiological process experienced by women and occurs during the first pregnancy, and attenuation nausea and vomiting are normal symtoms and are often found in the first trimester og pregnancy. 2022 this research is quantitative in nature using an analytical research design using a cross sectional approach, the number of samples is 30 responden. The results of the analysis use the wi Chi square with an a 0,05 a df I and p value 0,038 (p<0,05) attina there is a pantesal chard and gestational age with hyperemesis gravidarum. There is a significant relationship between parity and hyperemesis gravidarum. The results of the analysis using the Chi-square test with a 0.05 woth df = 2 and p value 0,05 the hypothesis wichh states that there is a relationship between parity and hyperemesis gravidarum is proven statisticallyKeyword : Parity, Gestational age, Hyiperemesis Gravidarum